Greenhouse gas mitigation guidelines for dairy farmers in China Training Material - Wang, Wei (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
Training material from the CCAFS Project "Upscaling promising livestock options for mitigating greenhouse gas emissions in Asia". The material includes a report on mitigation options for feed management, a report on mitigation options for manure management, and a report on the total farm approach and a brief for term explanations.